What Counts as Creativity in Education? An Inquiry into the Intersections of Public, Political, and Policy Discourses - Perry, Mia; Collier, Diane R. (Canadian Journal of Education/Revue canadienne de l'éducation, 2018)
In this essay, the authors examine the varied public, everyday, and academic discourses of creativity that combine to influence our current educational goals and policies, particularly in North America and Europe. From Sir Ken Robinson’s (2006) cutting remark that “Schools kill creativity!” to the Action Canada Foundation’s (2013) assessment that creativity is one of the seven core learning competencies required in the 21st century, this article portrays the compelling push and pull of creativity in education today. The authors found themselves in search of this seemingly crucial, yet increasingly undersupported aspect of their work in teacher education and research. Coming from literacy and arts education, the authors were called to question what they had always taken for granted. This article contextualizes creativity amid everyday, public, and academic discourses. Through engaging in this inquiry, the extent to which creativity is the recipe fo success, as it is so often deemed to be, is assessed and a conceptual framework for creativity in action is proposed.